An Integrated Solution For An Integrated Water Resource Management Of Lake Victoria Basin (LVB) - Odongtoo, Godfrey; Lating, Peter Okidi; Ssebuggwawo, Denis (Annals of Valahia University of Targoviste. Geographical Series, 2019)
Lake Victoria Basin is a very important resource for the five riparian countries: Uganda, Kenya, Tanzania, Rwanda and Burundi. The Lake Victoria Basin provides resources for fishing, agriculture, medicine, forestry, water transport and other economic activities. However, its surrounding is affected by population growth, urbanization, industrialization, increasing commercial activities and inadequate provision of sanitation services among others. These grossly affect the landscape and water resources around the lake basin. In this paper, a web based integrated solution prototype is presented. The system consists of web access, mobile access, web service handler, mobile service handler and a database. It can be used to address communication challenges by enhancing stakeholder’s participation, information sharing and enforcement of laws by timely communication and coordination of activities of good governance. The test results confirm that the system is effective and can be used to operate in real world environment in the management of water resources by providing the key actors with relevant information to facilitate decision making.
Keywords: Communication, Information Sharing, Lake Victoria Basin, Integrated Water Resource Management, Integrated solution.